Identification of Major Organisms Involved in Nutritional Ecosystem in the Acidic Soil From Pennsylvania, USA - James, Madison T.; Farrisi, Sophia T.; Shah, Shreya; Shah, Vishal (Frontiers in Environmental Science, 2022)
Microorganisms play a critical role in the structure and functioning of soil ecosystems. Within acidic soil across the northeastern United States and Canada, we have little understanding of the microbial diversity present and its relationship to the biochemical cycles. The current study is aimed at understanding the taxonomical and functional diversities in the acidic soil obtained from near various types of trees, how the diversities change as a function of depth, and the linkage between taxonomical and functional diversities. From eight sampling locations, soil samples were collected from three horizons (depths). The three depths were 0–10 cm (A), 11–25 cm (B), and 26–40 cm (C). Results indicate that across all the samples analyzed, Bradyrhizobium and Candidatus Solibacter are the most abundant bacteria in the soil microbiome. The differences in the soil microbiome across the samples were attributed to the abundance of individual organism’s present in the soil and not to the presence or absence of individual organisms. Subsystem level analysis of the soil microbiome sequences indicate that there is higher level of abundance of genes attributed to regulation and cell signaling. A low level of sequences were detected for sulfur metabolism, potassium metabolism, iron acquisition and metabolism, and phosphorous metabolism. Structure-functional analysis indicate that Bradyrhizobium, Rhodopseudomonas, and Burkholderia are the major organisms involved in the nutritional ecosystem functioning within acidic soil. Based on the results, we propose utilizing a consortium of these organisms as an environmentally friendly alternative to the use of chemicals to maintain soil fertility and ecosystem functioning.